A Family of Superhelicenes: Easily Tunable, Chiral Nanographenes by Merging Helicity with Planar pi Systems - Reger, David; Haines, Philipp; Amsharov, Konstantin; Schmidt, Julia A.; Ullrich, Tobias; Bönisch, Simon; Hampel, Frank; Görling, Andreas; Nelson, Jenny; Jelfs, Kim E.; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2021)
We designed a straightforward synthetic route towards a full-fledged family of pi-extended helicenes: superhelicenes. They have two hexa-peri-hexabenzocoronenes (HBCs) in common that are connected via a central five-membered ring. By means of structurally altering this 5-membered ring, we realized a versatile library of molecular building blocks. Not only the superhelicene structure, but also their features are tuned with ease. In-depth physico-chemical characterizations served as a proof of concept thereof. The superhelicene enantiomers were separated, their circular dichroism was measured in preliminary studies and concluded with an enantiomeric assignment. Our work was rounded-off by crystal structure analyses. Mixed stacks of M- and P-isomers led to twisted molecular wires. Using such stacks, charge-carrier mobilities were calculated, giving reason to expect outstanding hole transporting properties.
CRIS-Team WoS Importer:2021-07-23

A Functional Hexaphenylbenzene Library Comprising of One, Three, and Six Peripheral Rylene-Diimide Substituents - Dusold, Carolin; Platzer, Benedikt; Haines, Philipp; Reger, David; Jux, Norbert; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
Synthesis and characterization of a series of rylene-diimide substituted hexaphenylbenzenes (HPBs) is presented. The direct connection of the rylene-diimide units to the HPBs via the imide-N-position without any linkers as well as the use of naphthalene-diimides (NDIs) next to perylene-diimides (PDIs) is unprecedented. While mono-substituted products were obtained by imidization reactions with amino-HPB and the respective rylene-monoimides, key step for the formation of tri- and hexa-substituted HPBs is the Co-catalysed cyclotrimerization. Particular emphasis for physic-chemical characterization was on to the number of NDIs/PDIs per HPB and the overall substitution patterns. Lastly, Scholl oxidation conditions were applied to all HPB systems to generate the corresponding hexa-peri-hexabenzocoronenes (HBCs). Importantly, the efficiency of the transformation strongly depends on the number of NDIs/PDIs. While three rylene-diimide units already hinder the Scholl reaction, the successful synthesis of mono-substituted HBCs is possible.
CRIS-Team WoS Importer:2021-01-15

Anticancer Effect of an Electronically Coupled Oligoferrocene - Zeh, Gina; Haines, Philipp; Miehlich, Matthias; Kienz, Torben; Neidlinger, Andreas; Friedrich, Ralf P.; Alexiou, Christoph; Hampel, Frank; Guldi, Dirk Michael; Meyer, Karsten; Schatz, Jürgen; Heinze, Katja; et al. (Organometallics, 2020)
The mode of anticancer activity of simple ferrocenes often relies on their intracellular oxidation with the formation of cytotoxic ferrocenium species. The former compounds should be considered as prodrugs and derived from them ferroceniums as drugs. The drugs are 17e- organometallic species. Therefore, they are chemically unstable and decompose with formation of free cyclopentadienyl ligands (which are further transformed to more stable species) and iron ions. The short lifetime of ferrocenium drugs limits the anticancer effect of ferrocene prodrugs. In this paper we prepared a series of acylated aminoferrocene monomers, dimers, and higher oligonuclear complexes FcN (where N = 1-4). Drugs [FcN]+ derived from FcN (N > 1) are more stable than monomeric [Fc]+, provided that the ferrocene units are electronically coupled. Correspondingly, we expected that FcN species will be more potent anticancer agents in comparison to the related monomers. These assumptions were confirmed for dimer 10. We observed that this prodrug has sufficient solubility in aqueous solution (100 μM) and favorable lipophilicity (log P = 2.2 ± 0.2). Ferrocene units in 10 are efficiently electronically coupled via a -C(═O)NH- linker according to cyclic voltammetry, differential pulse voltammetry, and spectroelectrochemistry. We observed that 10 is the most efficient catalyst of the production of reactive oxygen species (ROS) and the most active anticancer agent in comparison to control monomers and their mixtures.
CRIS-Team Scopus Importer:2020-09-14

Electronic Communication across Porphyrin Hexabenzocoronene Isomers - Martin, Max; Lungerich, Dominik; Haines, Philipp; Hampel, Frank; Jux, Norbert (Angewandte Chemie International Edition, 2019)
Single-molecule electronic components (SMECs) are envisioned as next-generation building blocks in quantum circuit systems. However, challenges such as the reproducibility of the electrode attachment to the individual molecules hamper their fundamental investigation. For our purpose, we introduced quasi optoelectronic electrodes (QOEs) that allow for rapid investigations of the properties and suitability of compounds for molecular electronic devices. In particular, we probed hexa-peri-hexabenzocoronene (HBC) as a model system for D6h-symmetrical nanographenes, with porphyrins as QOEs attached to the periphery. We prepared selectively bis-porphyrin-functionalized HBCs with ortho-, meta- and para-substitution and studied their communication properties, in correlation to the geometrical alignment and size of the system, by electrochemistry and optical spectroscopy. Further insights into structure–property relationships were gained by DFT calculations and X-ray diffraction analysis.
CRIS-Team Scopus Importer:2019-06-04
Keywords: exchange interactions; hydrocarbons; molecular electronics; porphyrinoids; UV/Vis spectroscopy

Exploring Tetrathiafulvalene–Carbon Nanodot Conjugates in Charge Transfer Reactions - Ferrer-Ruiz, Andres; Scharl, Tobias; Haines, Philipp; Rodriguez-Perez, Laura; Cadranel, Alejandro; Herranz, M. Angeles; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2018)
Carbon nanodots (CNDs) were synthesized using low-cost and biocompatible starting materials such as citric acid/urea, under microwave irradiation, and constant pressure conditions. The obtained pressure-synthesized CNDs (pCNDs) were covalently modified with photo- and electroactive π-extended tetrathiafulvalene (exTTF) by means of a two-step esterification reaction, affording pCND-exTTF. The electronic interactions between the pCNDs and exTTF were investigated in the ground and excited states. Ultrafast pump–probe experiments assisted in corroborating that charge separation governs the deactivation of photoexcited pCND-exTTF. These size-regular structures, as revealed by AFM, are stable electron donor–acceptor conjugates of interest for a better understanding of basic processes such as artificial photosynthesis, catalysis, and photovoltaics, involving readily available fluorescent nanodots.
CRIS-Team Scopus Importer:2022-04-14
Keywords: carbon nanodots; charge transfer; donor–acceptor systems; excited state dynamics; tetrathiafulvalene

Fine-tuning the assemblies of carbon nanodots and porphyrins - Scharl, Tobias; Cadranel, Alejandro; Haines, Philipp; Strauß, Volker; Bernhardt, Sarah; Vela, Sonia; Atienza, Carmen; Gröhn, Franziska; Martin, Nazario; Guldi, Dirk Michael (Chemical Communications, 2018)
We present charge-transfer assemblies of electron accepting, pressure-synthesized carbon nanodots (pCNDs) and an electron donating porphyrin. Amidine derivatization of the porphyrin allows for hydrogen bonding interactions with the carboxyl groups on the surface of pCNDs, which drive the formation of the assembly. Upon photoexcitation, this electron donor-acceptor supramolecular construct features ultrafast charge separation, and subsequent charge recombination in 27 ps.
CRIS-Team Scopus Importer:2022-04-14

Helically and Linearly Fused Rylenediimide-Hexabenzocoronenes - Dusold, Carolin; Haines, Philipp; Platzer, Benedikt; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
Perylene- as well as naphthalenediimides were fused to hexabenzocoronenes (HBCs) at their imide position to realize highly π-extended donor–acceptor (D–A)-hybrids. Successful isomer separation in the first step was decisive to guarantee a straightforward synthetic sequence. Hexaphenylbenzenes as precursors were accessed via Diels–Alder reactions and reacted in a Scholl oxidation to yield the respective HBC derivatives. The fully conjugated benzimidazole linker, which separates the electron donating HBC from the electron accepting rylenediimide, enabled the formation of either a linear or a helical configuration. Largely different chemical, physical, and optoelectrical characteristics were noted for the two configurations. What stood out was their aggregation and their excited state deactivation depending on the solvent polarity. Results from global analysis of the femtosecond transient absorption data corroborated the formation of a charge-transfer (CT) state that is stabilized in the helically fused configuration relative to the linear analogue. However, a comparison with spectroelectrochemical experiments failed to disclose evidence for a charge-separated (CS) state.
CRIS-Team Scopus Importer:2021-03-19
Keywords: charge transfer; helicene; hexabenzocoronene HBC; rylenediimide; transient absorption

How To Make Nitroaromatic Compounds Glow: Next-Generation Large X-Shaped, Centrosymmetric Diketopyrrolopyrroles - Skonieczny, Kamil; Papadopoulos, Ilias; Thiel, Dominik; Gutkowski, Krzysztof; Haines, Philipp; McCosker, Patrick Michael; Laurent, Adele D.; Keller, Paul A.; Clark, Timothy; Jacquemin, Denis; Guldi, Dirk Michael; Gryko, Daniel T. (Angewandte Chemie International Edition, 2020)
Red-emissive pi-expanded diketopyrrolopyrroles (DPPs) with fluorescence reaching lambda=750 nm can be easily synthesized by a three-step strategy involving the preparation of diketopyrrolopyrrole followed by N-arylation and subsequent intramolecular palladium-catalyzed direct arylation. Comprehensive spectroscopic assays combined with first-principles calculations corroborated that both N-arylated and fused DPPs reach a locally excited (S-1) state after excitation, followed by internal conversion to states with solvent and structural relaxation, before eventually undergoing intersystem crossing. Only the structurally relaxed state is fluorescent, with lifetimes in the range of several nanoseconds and tens of picoseconds in nonpolar and polar solvents, respectively. The lifetimes correlate with the fluorescence quantum yields, which range from 6 % to 88 % in nonpolar solvents and from 0.4 % and 3.2 % in polar solvents. A very inefficient (T-1) population is responsible for fluorescence quantum yields as high as 88 % for the fully fused DPP in polar solvents.
CRIS-Team WoS Importer:2020-07-24

On the photophysics of nanographenes-investigation of functionalized hexa-: Peri -hexabenzocoronenes as model systems - Haines, Philipp; Reger, David; Träg, Johannes; Strauss, Volker; Lungerich, Dominik; Zahn, Dirk; Jux, Norbert; Guldi, Dirk Michael (Nanoscale, 2021)
In this study, we report on hexa-peri-hexabenzocoronenes (HBCs) as representative models for nanographenes. To this end, we synthesized a family of functionalized HBCs and investigated the impact of the substituents on the π-extended systems of the HBCs. DFT and TD-DFT calculations suggested a charge transfer character, which intensified as the electron density withdrawing effects of the substituents (-M-effect) increased. Unambiguous corroboration of the charge transfer character in the case of NO2-substituents was realized via steady-state absorption and fluorescence experiments, which focused on the dependencies on the solvent polarity and temperature featuring. Going beyond HBCs with NO2-substituents, time-correlated single photon counting, and femtosecond and nanosecond transient absorption spectroscopy unveiled long-lived singlet and triplet excited states. As a complement, we performed electrochemical and spectroelectrochemical measurements. These measurements were carried out to shed light onto the nature of the functionalized HBCs as electron acceptors and/or donors, on the one hand, and their corresponding spectroscopic signatures, on the other hand. All of the aforementioned information enabled intermolecular charge separation assays with, for example, suitable electron acceptors by steady-state and time-resolved spectroscopy. This journal is
CRIS-Team Scopus Importer:2021-02-05

Oxa[7]superhelicene: A pi-Extended Helical Chromophore Based on Hexa-peri-hexabenzocoronenes - Reger, David; Haines, Philipp; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2018)
A novel pi-extended "superhelicene" based on hexa-peri-hexabenzocoronenes (HBCs) has been synthesized by an efficient four-step synthetic procedure starting from diphenyl ether. Comprehensive structural analysis of the helicene was performed by NMR spectroscopy and mass spectrometry measurements together with X-ray analysis. Physicochemical analysis of the superhelicene and suitable HBC references revealed it had outstanding fluorescent features with quantum yields of over 80%.
Keywords: fluorescence; helical structures; photophysics; polycyclic aromatic hydrocarbons; pi-extension

Photon- and Charge-Management in Advanced Energy Materials: Combining 0D, 1D, and 2D Nanocarbons as well as Bulk Semiconductors with Organic Chromophores - Cadranel, Alejandro; Haines, Philipp; Kaur, Ramandeep; Menon, Arjun; Münich, Peter Wilhelm; Schol, Peter; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
In this contribution, seminal works in the area of photon- and charge-management are highlighted with focus on covalent electron donor-acceptor conjugates built around porphyrins (Ps), on one hand, and 0D, 1D, and 2D nanocarbons, on the other hand. Photons in these conjugates are managed by Ps, while 0D, 1D, and 2D nanocarbons serve as the active component, which enable managing charges. With a few leading examples, it can be explored much beyond the simple photon- and charge-management characterization and emphasize photovoltaics and photocatalysis to convert and store energy. This contribution concludes by highlighting recent progress in mixing and matching the unique charge-management features of nanocarbons in the design of multidimensional nanocarbons.
CRIS-Team Scopus Importer:2020-12-11
Keywords: charge management; nanocarbons; photon management; solar-energy conversion

Probing Charge Management across the π-Systems of Nanographenes in Regioisomeric Electron Donor-Acceptor Architectures - Hölzel, Helen; Haines, Philipp; Kaur, Ramandeep; Lungerich, Dominik; Jux, Norbert; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Inspired by light-induced processes in nature to mimic the primary events in the photosynthetic reaction centers, novel functional materials combine electron donors and acceptors, i.e., (metallo)porphyrins (ZnP) and fullerenes (C60), respectively, with emerging materials, i.e., nanographenes. We utilized hexa-peri-hexabenzocoronene (HBC) due to its versatility regarding functionalization and physicochemical properties, to construct three regioisomeric ZnP-HBC-C60 conjugates, which foster geometrical diversity by arranging ZnP and C60 in ortho-, meta-, and para-positions to each other. The corresponding hexaarylbenzene (HAB) motifs, with an interrupted π-system, were also prepared. Transient absorption measurements disclosed the fast population of charge transfer as well as singlet and triplet charge-separated states. With the help of density functional theory (DFT) calculations, we further conceive the communication across the HBCs and HABs. This work reveals the impact of both the geometrical arrangement with respect to through-space versus through-bond interactions and the structural rigidity/flexibility on the charge management across the different π-systems.
CRIS-Team Scopus Importer:2022-06-10

Purification and structural elucidation of carbon dots by column chromatography - Hinterberger, Vanessa; Damm, Cornelia; Haines, Philipp; Guldi, Dirk Michael; Peukert, Wolfgang (Nanoscale, 2019)
Carbon dots (CDs) are an astonishing class of fluorescent materials with many applications in bioimaging, drug delivery, photovoltaics and photocatalysis due to their outstanding luminescence properties and low toxicity. However, the internal CD structure of bottom-up synthesized CDs is still the subject of considerable debate. Unambiguous analysis of the internal CD composition is hampered by the fact that reaction products usually contain mixtures of several CD fractions as well as molecular intermediate and side products. Therefore, purification and careful separation of the various CD fractions is vital for structural analysis and isolation of pure CDs possessing optimized optical properties. In this study, CD solutions were synthesized from citric acid and cysteine via a one-pot hydrothermal synthesis. A simple column chromatography unit was used to systematically study the influence of the molar precursor ratios and synthesis conditions (temperature, reaction time) on the CD solution composition. By investigating the structural and optical properties of the chromatographically separated fractions, three different fluorescent species could be identified. Freely floating molecular fluorophores left the column first, followed by highly fluorescent CDs with fluorophores bound to the carbon core, finally followed by low-fluorescent carbon particles without fluorophores. We demonstrate that the CD solution composition and the internal structure of the individual fluorescent components can be clarified via chromatographic separation. This information can be further applied to isolate pure CDs with optimized optical properties.
CRIS-Team Scopus Importer:2019-05-09

Screening Nanographene-Mediated Inter(Porphyrin) Communication to Optimize Inter(Porphyrin–Fullerene) Forces - Haines, Philipp; Kaur, Ramandeep; Martin, Max; Minameyer, Martin; Frühwald, Stefan; Bönisch, Simon; Lungerich, Dominik; Hampel, Frank; Görling, Andreas; Drewello, Thomas; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2021)
Multifunctional molecular materials comprising porphyrins and fullerenes have served as perfect prototypes to study key aspects of natural photosynthesis starting at light harvesting and energy transfer processes all the way to charge separation, charge shift, and charge recombination. Herein, hexa-peri-hexabenzocoronenes (HBCs) are explored, decorated with one, two, and six porphyrins at their peripheral positions, within the context of replicating key steps of photosynthesis. The major focus of the investigations is to screen inter(porphyrin) communications across the HBC platform as a function of the substitution pattern and to optimize the intermolecular forces with fullerenes. To this end, the ground- and excited-state features are investigated in the absence of C60 and C70 by employing an arsenal of spectroscopic methods. Further insights into inter(porphyrin) communications come from time-dependent density-functional theory (TDDFT) calculations. In the presence of C60 and C70, X-ray crystallography, steady-state and time-resolved spectroscopy, and mass spectrometry corroborate exceptionally strong inter(porphyrin–fullerene) interactions in the solid, liquid, and gas phases. The experiments are backed-up with DFT calculations of the geometrically optimized and energetically stable complex configuration.
CRIS-Team Scopus Importer:2021-03-26
Keywords: charge separation; crystal structure; fullerene; hexabenzocoronene; porphyrin; transient absorption

Singlet Fission in Carbene-Derived Diradicaloids - Ullrich, Tobias; Pinter, Piermaria; Messelberger, Julian; Haines, Philipp; Kaur, Ramandeep; Hansmann, Max M.; Munz, Dominik; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2020)
Herein, we present a new class of singlet fission (SF) materials based on diradicaloids of carbene scaffolds, namely cyclic (alkyl)(amino)carbenes (CAACs). Our modular approach allows the tuning of two key SF criteria: the steric factor and the diradical character. In turn, we modified the energy landscapes of excited states in a systematic manner to accommodate the needs for SF. We report the first example of intermolecular SF in solution by dimer self-assembly at cryogenic temperatures.
CRIS-Team WoS Importer:2020-04-07

Synthesis and excited state processes of arrays containing amine-rich carbon dots and unsymmetrical rylene diimides - Đorđević, Luka; Haines, Philipp; Cacioppo, Michele; Arcudi, Francesca; Scharl, Tobias; Cadranel, Alejandro; Guldi, Dirk Michael; Prato, Maurizio (Materials Chemistry Frontiers, 2020)
Combining carbon dots (CDs) with π-extended chromophores is an attractive way to study the electronic and energy processes of the former as a key step to many applications, including photosensing, photocatalysis, or photosensitization. CDs, in conjugation with chromophores, can have value in preparing donor-acceptor hybrids, and can also be used as scaffolds to support electronic communication between dyes. In this work, we conjugate two different rylene diimides, naphthalene and perylene diimides (NDI and PDI, respectively), with amorphous nitrogen-doped carbon dots. We take advantage of the imidization reaction between the amine-rich surface of the carbon dots and the monimide monoanhydride precursors of NDIs and PDIs, under microwave assisted conditions. The resulting (nano)hybrids were characterized also by spectroscopic methods. In particular, time-resolved spectroscopy for the multichromophoric array, consisting of CDs and both rylene diimides, allowed us to elucidate the complex inter-chromophoric interactions taking place in the excited state.
CRIS-Team Scopus Importer:2020-12-11

Using carbon nanodots as inexpensive and environmentally friendly sensitizers in mesoscopic solar cells - Margraf, Johannes; Lodermeyer, Fabian; Strauß, Volker; Haines, Philipp; Walter, Johannes; Peukert, Wolfgang; Costa, Ruben Dario; Clark, Timothy; Guldi, Dirk Michael (Nanoscale Horizons, 2016)
We discuss the use of carbon nanodots (CNDs) as sensitizers in mesoscopic solar cells. The CNDs are synthesized using a one-step, bottom-up microwave approach with citric acid, urea, and formic acid as precursors in aqueous media. Their light-harvesting capabilities can be tuned by adjusting the synthetic parameters. Comprehensive spectroscopic and theoretical studies allow us to rationalize the nature of their absorption features. Promising power conversion efficiencies ( extgreekh) of 0.24% can be achieved from these cheap and eco-friendly sensitizers by optimizing the solar-cell assembly process. Interestingly, we found that extending the light absorption towards longer wavelengths does not necessarily improve the performance of the solar cells, since the longer-wavelength absorption features hardly contribute to the cells' photo-action spectra, so that the overall power conversion efficiency is actually worse. The origin of the lower performance is corroborated in transient absorption spectroscopy and photovoltage decay measurements. Our work points, on one hand, to the limits of as-synthesized CNDs as photosensitizers and, on the other hand, to possible improvements.

Well-separated water-soluble carbon dots via gradient chromatography - Michaud, Vanessa; Pracht, Jonas; Schilfarth, Fabian; Damm, Cornelia; Platzer, Benedikt; Haines, Philipp; Harreiß, Christina; Guldi, Dirk Michael; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2021)
Carbon dots (CDs) are strongly fluorescent advanced materials that are promising for applications in bio-imaging, sensors or luminescent displays. One of the most-widely used class of CDs is synthesized via an aqueous, bottom-up technique starting from citric acid (CA) and an amino-precursor. Very high fluorescence quantum yields (QY) are reported for the resulting CDs. The as-synthesized raw suspensions, however, are crude mixtures of many components: bare carbon cores, carbon cores functionalized with fluorophores, freely floating molecular fluorophores, and several other by-products. In this study, we synthesized CDs from CA and amino acid cysteine (Cys) hydrothermally and demonstrate a complete separation of all components by means of two step gradient chromatography. In the first step, the separation was carried out on a normal-pressure preparative silica-gel column to get sufficient amounts of material to investigate structure and optical properties of the collected fractions. This preparative gradient elution method enabled us to separate moderately-fluorescent CDs from freely floating molecular fluorophores, polymeric fluorophores and CDs with built-in fluorophores. Here, we evidenced that amorphous CDs co-exist with crystalline CDs in one and the same suspension and showed that the amount of crystalline CDs increases with the synthesis temperature. In the second step, we turned to high performance liquid chromatography (HPLC) to further improve and optimize the efficiency of purification and automate it. Via HPLC, we were able to well-separate of up to six components. Within this work, we laid the foundation for CD purification with the highest possible purity for aqueous, bottom-up synthesized CDs and quantified the true quantum yield of CDs.
Keywords: Graphene quantum dots; Photoluminescence mechanism; Polymer dots; Citric-acid; Nanodots; Fluorescence; Yield; Nitrogen; Light; Reduction